'And now it is the serpent's turn': the rhetoric of the figura serpentinata in Frank O'Hara's 'In Memory of My Feelings'. Issue 1 (2nd January 2016) - Ladkin, Sam
Abstract: 'In Memory of My Feelings' is widely regarded as one of Frank O'Hara's seminal works, but can we trust its finale? This article reads the conclusion of the poem in the light of the art-historical term ' figura serpentinata '. By doing so, we can learn something about the translation of formal tropes across aesthetic mediums (sculpture, painting, poetry), and disclose a queer genealogy within the development of the history of art. It includes readings of ancient statuary (including the Laocoön and His Sons, the Belvedere Torso and the Discobolus ) and Roman rhetoric (Quintilian) to trace the recovery of the figura serpentinata from interwoven aesthetic and rhetorical traditions during the Renaissance (Michelangelo Buonarroti) and the Enlightenment (Johann Joachim Winckelmann). The article also theorizes Johann Gottfried Herder's proto-phenomenological aesthetics as they prepare an argument for statuary as the elegiac accretion of earlier erotic desire. It describes the figure of the serpent and provides one final example contemporary to O'Hara in which the representation of the figura serpentinata is replaced by its performance in the painting of the Abstract Expressionist Jackson Pollock. It concludes with some comments on the turn between figuration in representation, abstraction and rhetoric.